الذكاء الضمني لدى طلبة جامعة بغداد - محمود جرجيس محمد, أسيل; زامل صالح, فاضل (Journal of College of Education, 2020)
The present research aims to investigate: Implicit intelligence for students at the university of Baghdad. Significant differences in implicit intelligence for students at the university of Baghdad in regard to gender and specialization variables. The basic sample of the research consisted of 650 (male / female ) students distributed among  24  collages ( humanities and scientific ). To achieve the research aims, implicit intelligence has been constructed as an instrument, The psychometric features  of the instruments have been computed. .  Means has been also used to treat the collected data statistically depending on (SPSS) The Findings show  that: Students at the university of the Baghdad have high level of implicit intelligence directed to malleable thought of intelligence There were significant statistical difference in the implicit intelligence in regard to gender variable for the benefit of female students and there was significant statistical difference in regard to the variable of specialization  and  the interaction  between gender and specialization. In the light of the above findings the research set a number of recommendations and suggestions.